THE ROLE OF SALINE SOLUTION PROPERTIES ON POROUS LIMESTONE SALT WEATHERING BY MAGNESIUM AND SODIUM SULFATES - Ruiz-Agudo E.; Mees F.; Jacobs P.; Rodriguez-Navarro C. (My University, 2007)
Saline solution properties, viscosity in particular, are shown to be critical in salt weathering associated with sodium and magnesium sulfate crystallization in porous limestone. The crystallization of sodium and magnesium sulfate within a porous limestone has been studied at a macro- and microscale using different techniques, including mercury intrusion porosimetry, environmental scanning microscopy and X-ray computed tomography. Such analysis enabled the visualization of the crystallization process in situ, and at high magnification, yielding critical information as to where and how salts crystallize. Sodium sulfate decahydrate (mirabilite) tends to crystallize in large pores as euhedral micron-sized crystals formed at low supersaturation near to the surface of the stone. In contrast, magnesium sulfate heptahydrate (epsomite) tends to precipitate as anhedral wax-like aggregates formed at high supersaturation and distributed homogeneously throughout the stone pore system filling large and small pores. While the former crystallization behavior resulted in scale formation, the latter led to crack development throughout the bulk stone. Ultimately, the contrasting weathering behavior of the two sulfates is explained by considering differences in flow dynamics of solutions within porous materials that are mainly connected with the higher viscosity of magnesium sulfate saturated solution (7.27 cP) when compared with sodium sulfate saturated solution (1.83 cP). On the basis of such results, new ways to tackle salt weathering, particularly in the field of cultural heritage conservation, are discussed.
Keywords: STONE DECAY; SODIUM SULFATE; MAGNESIUM SULFATE; SALT WEATHERING; ESEM